Effects of prepubertal to peripubertal exposure of triclosan on the reproductive health of the young male laboratory mice - Shobha Raj; Poonam Singh (Global Journal of Fertility and Research - Peertechz Publications, 2023)
Over the last few decades, a massive increase in environmental toxicants has played a significant role in causing hindrance in the process of sexual maturity, leading to impaired reproductive health. Several toxicants are existing in the environment because of rapid industrialization, agricultural activities, and urbanization that act as endocrine disrupting chemicals (EDCs). Triclosan (TCS; 2,4,4'-trichloro-2'-hydroxydiphenyl ether) is one of the EDCs, acts as an antimicrobial chemical, and is used widely in personal care products and several commercial preparations as preservatives. It is found to interfere with normal reproduction and sexual maturity. The present study is therefore, aimed to investigate the impact of prepubertal to peripubertal exposure of TCS (300 and 600 mg/kg BW/day from PND 22 to PND 63) to observe the age of the onset of puberty, weights of the reproductive organs, alterations in the levels of testicular cholesterol, serum testosterone, and histopathology of the testis in the young laboratory mice. TCS exposure caused a significant delay in the age of prepuce separation, an indicator of the onset of puberty. Its exposure from PND 22 to PND 63 resulted in significant reductions in the weights of the testis, epididymis, and seminal vesicle, levels of testicular cholesterol, and serum testosterone in the young mice at PND 64. Testicular histology of such mice also showed regressive changes in the seminiferous tubules, indicating the interference of TCS in the process of spermatogenesis. The findings of the present study, therefore, reveal that TCS delays the age of onset of puberty and interferes with the endocrine functions of the testis.